Role of subcutaneous drain in class III and class IV laparotomy wound - Patel, Pranav R.; Koyani, Himanshu B. (International Surgery Journal, 2019)
Background: Surgical site infections (SSI) are major problem in general surgery. Aim of this study is to know the role of subcutaneous conrrugated drain in class III and IV laparotomy wounds. Methods: Comparative study was done in 100 patients of emergency laparotomy in civil hospital, Gandhinagar from January 2014 to December 2016. Results: Incidence of surgical site infections were significantly lower (16%) in patients with subcutaneous drain, compared to 40% in patients without drain (p value 0.01). Conclusions: Corrugated subcutaneous drain is cost effective way of reducing surgical site infections and subsequent morbidities in class III and IV laparotomy wound.